Correlations and comparisons of teacher expectations achievement motivation academic achievement and creativity - Jun Hu; Shan Qian (Frontiers in Psychology)
IntroductionTeacher expectations are believed to play a critical role in shaping students’ academic achievement and creativity, yet the underlying psychological mechanisms remain insufficiently understood. This study investigates the mediating role of achievement motivation in the relationships between teacher expectations, academic achievement, and creativity among junior high school students, aiming to provide empirical insights for effective educational practices.MethodsA controlled experimental design was employed to examine the psychological effects of teacher expectations. The sample consisted of 583 students from urban and township junior high schools. Teacher expectations were measured using the Teacher Expectation Scale. Academic achievement was assessed via final examination scores in Chinese, mathematics, and English. Achievement motivation was evaluated with the Achievement Motivation Scale, and creativity was measured using a standardized creativity assessment. Data were analyzed using analysis of variance (ANOVA), correlation analysis, and structural equation modeling (SEM).ResultsTeacher expectations had a significant positive effect on academic achievement. Achievement motivation partially mediated the relationship between teacher expectations and academic achievement, and fully mediated the relationship between teacher expectations and creativity. The mediation models demonstrated strong fit, confirming the central role of motivation in translating teacher expectations into student outcomes.DiscussionThe findings confirm that teacher expectations influence both academic performance and creative development through motivational pathways. Achievement motivation serves as a key psychological mechanism that links external educational beliefs to internal student drives. These results support the implementation of teacher training and classroom strategies that foster positive expectations, thereby enhancing students’ motivation, academic success, and creative potential. This study contributes to the growing body of evidence advocating for supportive and expectancy-rich learning environments in secondary education.